Turnabout - Haddix, Margaret Peterson (New York : Simon & Schuster Books For Young Readers, 2000)
After secretly receiving injections at the age of 100 that are meant to reverse the aging process, Melly and Anny Beth grow younger until, as teenagers, they try to find a guardian to take care of them as they return to infancy.
Booklist
690
Accelerated Reader AR
Keywords: Science fiction; Science -- Experiments -- Juvenile fiction; Aging -- Juvenile fiction